Analysis of China's Aggressive Behavior in the South China Sea during the COVID-19 Pandemic (2020 – 2021) - Djuyandi, Yusa; Azmi, Mohammad Fazrulzaman; Dermawan, Windy (Universitas Teuku Umar, 2025)
China was the first country that affected by the COVID-19 pandemic. However, China showed aggressive behavior during that period toward the South China Sea. Meanwhile, countries in the region concentrated on handling the COVID-19 pandemic. This study explains China's strategies and tactics in exploiting the COVID-19 pandemic phenomenon to achieve its interests in the South China Sea. This study used a literature study method to explain this phenomenon. The selected literature is secondary data scattered in previous research and credible news related to the political dynamics in the South China Sea. The research finds that China combines soft power, such as medical supply assistance and vaccine diplomacy, with hard power to increase its influence at the regional and global levels, including in the South China Sea region. In addition to disputes, these tactics can increase regional tensions and threaten the peace and stability of the South China Sea. In addition, this phenomenon also shows a decline in the trust of the disputing countries in the recognition of each other's sovereignty and the international regime.